Do consumers continue to use O2O food delivery services in the post-pandemic era? roles of sedentary lifestyle - Yao, Pinyi; Osman, Syuhaily; Sabri, Mohamad Fazli; Zainudin, Norzalina; Li, Yezheng (Elsevier, 2023)
Online-to-offline food delivery (O2OFD) services have become popular worldwide, and consumers O2OFD usage and sedentary behavior have increased during the COVID-19 pandemic. However, whether consumers will continue to use O2OFD in the post-pandemic era is uncertain, and the relationship between a sedentary lifestyle and O2OFD usage is poorly understood to date. Therefore, this study aims to investigate consumers continued intention to use O2OFD in the post-pandemic era and their subsequent use behavior, as well as to explore the roles of sedentary lifestyle. A research model based on the unified theory of acceptance and use of technology 2 (UTAUT2), integrating network externalities and including sedentary lifestyle, was proposed. A two-stage online survey was conducted in China, with 409 eligible responses used in the data analysis. The results indicate that habit, perceived network size, and perceived complementarity were the main predictors of continued intention, whereas habit and continued intention were the primary determinants of use behavior. A sedentary lifestyle was positively related to O2OFD use behavior and moderated the effects of habit and continued intention on use behavior. In addition to its theoretical contributions, this study has implications for public policies, marketing strategies, and consumer well-being.